A Pilot Study on Dietary Approaches in Multiethnicity: Two Methods Compared - Romina Valentini; Maria Grazia Dalfrà; Michela Masin; Antonella Barison; Marcon Marialisa; Eva Pegoraro; Annunziata Lapolla (International Journal of Endocrinology)
Background. Medical nutritional therapy is the most important method for normalizing glucose levels in pregnancy. In this setting, there is a new problem to consider relating to migrants, their personal food preferences, and ethnic, cultural, and religious aspects of their diet. We compared maternal and fetal outcomes between two multiethnic groups of pregnant women, one adopting a food plan that included dishes typical of the foreign women's original countries (the “ethnic meal plan” group), while the other group adopted a standard meal plan. Findings. To develop the meal plan, each dish chosen by the women was broken down into its principal ingredients. The quantity of each food was given in tablespoons, teaspoons, slices, and cups, and there were photographs of the complete dish. The group treated with the ethnic meal plan achieved a better metabolic control at the end of the pregnancy and a lower weight gain (though the difference was not statistically significant). As for fetal outcome, the group on the ethnic meal plan had babies with a lower birth weight and there were no cases of macrosomia or LGA babies. Conclusions. This preliminary study indicates the positive effect of an ethnic approach to diet on the outcome of pregnancy.